Analisis Yuridis Pengaturan Sumber Keuangan dalam Undang-Undang Nomor 2 Tahun 2008 tentang Partai Politik terhadap Eksistensi Partai Politik di Pemilihan Umum - Simanjuntak, Pran Mario; Artina, Dessy; Diana, Ledy (Peneliti.net, 2023)
The regulation of the financial resources of political parties is no longer relevant because parties make the existing financial resources to only care about the interests of donors. In the regulation, it is mentioned how membership fees become a source of party finance, but this has an impact on the problem of growing corruption cases in return for returning party capital. It also occurs in legitimate donations which cause the same problem. Meanwhile, party financial resources from APBN/APBD can only be used for political party regeneration education. This deviant situation makes political parties lose their existence to maintain democracy and popular sovereignty in general elections. The purpose of this research is to find out the urgency of the system of regulating political parties in general elections, the implications of the impact of current arrangements on the existence of political parties in general elections, and ideal ideas. The research method used in this research is normative legal research. This research is a library legal research. The focus of this research discussion is related to legal principles. The data sources used are primary, secondary, and tertiary legal sources. In this legal research, researchers use a statutory approach that will examine the law starting from the 1945 Constitution, the General Election Law to the Political Party Law. From the results of the research there are 3 main things that can be concluded. First, the urgency of political party financial resources to create legal certainty to the party between legitimate and illegitimate funds. The regulation creates systematisation in financial sources and limits related to the classification of financial sources obtained. Second, the regulation of party financial resources consisting of membership fees, APBN / APBD budgets, and legitimate donations, has currently reduced the existence of political parties in general elections. APBN/APBD financial sources that cannot be used during general elections create parties that are not transparent in finance, making parties arbitrary in finding and getting money or using it. Finally, the author lists some of the efforts the author offers in maintaining the existence of political party needs related to financial resources in general elections.